9. Dilema ASEAN Way dalam Penanganan Pencari Suaka Rohingya di Asia Tenggara - Annisa Wuryandari; Hermini Susiatiningsih; Nadia Farabi (Journal of International Relations Diponegoro, 2017)
ASEAN as a regionalism has its own region problematic, that is Rohingya asylum seekers which commenced from the domestic conflict of Myanmar yet subsequently spread into a regional issue. ASEAN Way evokes a dilemma due to the non-interference principle that restricts such efforts and behaviors of the institution in handling the issue of Rohingya asylum seekers. The purpose to determine ASEAN efforts, with its ASEAN Way, to overcome the dilemma which has emerged in handling the issue of Rohingya asylum seekers yet inflict to regional destabilization. Written in Constructivist Paradigm and Logic of Appropriateness Concept, ASEAN Way dilemma uses consensus as a peaceful settlement of dispute at a time of universal human rights deployed globally in handling the issue of the Rohingya asylum seekers. The result of this research indicates there is a normative alteration in ASEAN Way in accordance with the standard of appropriate behaviors in global and social context of the universal human rights.